You are on page 1of 4

ECEN 314: Signals and Systems

Solutions to HW 10
1. (4.3)(a) Note that the period of x1 (t) = sin(2t + 4 ), is T = 1. Hence the fundamental
frequency, o = 2. Also

1 j(2t+ )
j(2t+ 4 )
4 e
e
2j
1 j/4 j(2t)
1
=
e
e
ej/4 ej(2t)
2j
2j

x1 (t) =

Therefore, a1 = 2j1 ej/4 , and a1 = 1


ej/4 . The corresponding Fourier transform X1 (j)
2j
of x1 (t) is given by (Refer Sec 4.2 of the text),
X1 (j) = 2a1 ( o ) + 2a1 ( + o )
= (/j)ej/4 ( 2) (/j)ej/4 ( + 2)

(b) Note that the period of x2 (t) = 1 + cos(6t + 8 ), is T = 1/3. Hence the fundamental
frequency, o = 6. Also

1 j(6t+ )
j(6t+ 8 )
8 + e
e
2
1
1
= 1 + ej/8 ej(6t) + ej/8 ej(6t)
2
2

x2 (t) = 1 +

Therefore, a0 = 1, a1 = 12 ej/8 , and a1 = 12 ej/8 . The corresponding Fourier transform


X2 (j) of x2 (t) is given by,
X2 (j) = 2a0 () + 2a1 ( o ) + 2a1 ( + o )
= 2() + ej/8 ( 6) + ej/8 ( + 6)

2. (4.4) (a) The inverse Fourier transform is


Z

1
2() + ( 4) + ( + 4) ejt
x1 (t) =
2

1
=
2 + ej4t + ej4t
2
= 1 + cos(4t)
1

(b) The inverse Fourier transform is

Z
1
x2 (t) =
X2 (j)ejt d
2
Z 2
Z 0
1
1
jt
=
2e d +
(2)ejt d
2
2 2
2jt 0

= e 1 /(jt) 1 e2jt /(jt)

3. (4.10) Note that


Y(jw)

A(jw)

B(jw)

1 0 1

2
2

0
m

sin t
Y (j) (Refer fig)
t

sin t
1

Y (j) Y (j)
t
2
This is shown as A(j) in the figure with f = 1/. Using Table 4.1,we may write

2
d
sin t
j A(j)
t
t
d
which is B(j) shown in the figure (with m = j/2).
(b) Using Parsevals relation:
4
Z
Z
1
1
2 sin t
t
=
|B(j)|2 d = 3
t
2
2

4. (4.12)(a) From Example 4.2, we know that


2
1 + 2

e|t|

Using the differentiation property, we get

d
2
4j
|t|
te
j
=

.
d 1 + 2
(1 + 2 )2

(b) What we have shown in part (a) above is:


te

|t|

1
=
2

4j
ejt d
(1 + 2 )2

Interchanging t and in the above equation gives us:


Z
2e

||

4jt
ejt dt
2
2
(1 + t )

Replacing by above yields:


Z
2e|| =

4jt
ejt dt
(1 + t2 )2

Multiplying the above equation by j on both sides gives:


Z
2je

||

4t
ejt dt
(1 + t2 )2

which is precisely the Fourier Transform of

4t
.
(1+t2 )2

5. (4.26) (a)
(i) We have
Y (j) = X(j)H(j)

1
1
=
(2 + j)2 4 + j
1/4
1/4
1/2
=

+
4 + j 2 + j (2 + j)2
3

Hence, y(t) = (1/4)e4t u(t) (1/4)e2t u(t) + (1/2)te2t u(t)


(ii) We have
Y (j) = X(j)H(j)

1
1
=
(2 + j)2 (4 + j)2
1/4
1/4
1/4
1/4
=
+

+
2
2 + j (2 + j)
4 + j (4 + j)2
Hence, y(t) = (1/4)e2t u(t) + (1/4)te2t u(t) (1/4)e4t u(t) + (1/4)te4t u(t).
(iii) We have
Y (j) = X(j)H(j)

1
1
=
(1 + j) (1 j)
1/2
1/2
=
+
1 + j (1 j)
Hence, y(t) = (1/2)e|t| .
(b) Direct convolution of x(t) with h(t) yields:

0
t < 1,

(t1)
1e
1 < t 5,
y(t) =
(t5)
e
e(t1)
t > 5.
Taking the FT of y(t) gives
2ej3 sin(2)
(1 + j)
2j j
e
e 2 sin 2
=
1 + j

= X(j) H(j)

Y (j) =